2020
DOI: 10.1183/23120541.00528-2020
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of asthma exacerbation and management: a qualitative study of severe asthma

Abstract: BackgroundExacerbation is a defining feature of severe asthma, and oral corticosteroids (OCSs) are frequently prescribed to manage exacerbations. This qualitative study was conducted to examine the experience of patients with severe asthma, with a focus on asthma exacerbation and OCS treatment.MethodsAdults with severe asthma were recruited from three tertiary hospitals in South Korea. Data were collected through in-depth qualitative interviews. Verbatim transcripts were analysed using Colaizzi's phenomenologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“… 27 A recent qualitative study in severe asthmatics described the psychologic side effects of OCS, such as mood swings and anxiety derived from OCS reliance. 28 In our data, the prevalence of hypertension, osteoporosis, and diabetes mellitus were similar between the OCS-dependent group and the OCS-independent group.…”
Section: Discussionsupporting
confidence: 61%
“… 27 A recent qualitative study in severe asthmatics described the psychologic side effects of OCS, such as mood swings and anxiety derived from OCS reliance. 28 In our data, the prevalence of hypertension, osteoporosis, and diabetes mellitus were similar between the OCS-dependent group and the OCS-independent group.…”
Section: Discussionsupporting
confidence: 61%
“…Song et al, conducted a study of 21 patients having acute exacerbation of asthma. 20 The authors found that breathlessness and cough were the most common presenting complaints of the patients presenting with acute exacerbation. The authors also reported complications secondary to cough such as chest pain, inability to talk, and psychosocial problems associated with severe coughing.…”
Section: Discussionmentioning
confidence: 99%
“…Higher chronic use of OCS leads to increased risk of complications, costs, and dose-dependent mortality [16][17][18]. Furthermore, patients with severe asthma experience severe physical and psychological distress from exacerbations [19]. Nonetheless, physicians and regulatory authorities have not acknowledged the extent of the severe asthma burden.…”
Section: Epidemiology and Disease Burden In Koreamentioning
confidence: 99%